The Flouting of the Gricean Maxims in the Movies Insidious and Insidious 2 - Melinda Kurniati; Sharifah Hanidar (Lexicon, 2018)
The research attempts to examine the flouting of the Gricean maxims in two horror movies Insidious and Insidious 2. It also aims to investigate the functions of the flouting that the characters made when speaking to other characters. Qualitative and quantitative methods were used to analyze the data. The results show that in Insidious, the characters flout all the maxims with 23 cases of flouting: 3 cases of the flouting of the maxim of quality (13.1%), 9 cases of the flouting of the maxim of quantity (39.1%), 6 cases of the flouting of the maxim of relation (26.1%), and 5 cases of the flouting of the maxim of manner (21.7%). Whereas the characters in Insidious 2 only flout two maxims, the maxim of quantity and relation with 7 cases of floutings: 3 cases of the flouting of the maxim of quantity (42.8%), and 4 cases of the flouting of the maxim of relation (57.2%). The results indicate that characters in Insidious and Insidious 2 flout the maxims for a number of reasons, the main reasons being to avoid making the main characters upset, provide comprehensive explanations, convince the hearer, and criticize someone’s action.